Model Penguatan Subak di Era New Normal: Analisis Peran Collective Action pada Penerapan Sistem Terintegrasi Itik Padi di Tabanan-Bali - Vipriyanti, Nyoman Utari; Puspawati, Dewa Ayu; Yulianthi Sapanca, Putu Lasmi; Handayani Citra, Made Emy (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2020)
The Covid 19 pandemic has brought significant changes to the economy of Bali as a domestic and foreign tourist destination. The tourism sector, as the main contributor to the largest contributor to Gross Regional Domestic Product (GRDP), experienced a contraction, which had an impact on other sectors. One of the sectors affected in the agricultural sector, especially the marketing of food products. In the new normal era in Bali, it is necessary to strengthen the rural economy through the application of technology but the process of implementing these innovations is not always successful. The success of collective action is determined by the rational boundaries of society. The rational boundaries of society can be expanded by the presence of symmetrical information. The research objective was to analyze the role of collective action on the application of the Integrated System of Rice Ducks as an effort to increase farmers' income. This research is a case study in Subak Lanyah, Tabanan Sub District, Tabanan-Bali District. Primary data were collected through direct observation and questionnaires while secondary data were collected through literature studies. Analysis of the role of collective action in the application of the integrated system of rice ducks (STIP) was carried out statistically descriptive of farm costs and farmer income. The results showed that the STIP innovation as an effort to increase farmers' income was successfully implemented through Collective action. The collective action mechanism plays a role in strengthening social capital which encourages the application of STIP technology so that the income of Subak member farmers in Subak Lanyah, Tabanan-Bali increases. The success in implementing STIP technology is done by building a process of communication, trust, and networks of farmers with the government, private sector, and universities.of communication, trust, and networks of farmers with the government, private sector, and universities.